Analysis of calculating the fault current on the generator In Power System - Arnawan Hasibuan; Novra; Zulhiz Tami; Marya Ulfa; Alpaslan DURMUS (Faculty of Engineering, Malikussaleh University, 2024)
Short circuit fault current in the electric power system is one of the problems that can threaten the reliability and safety of system operations. This disturbance, which occurs due to direct contact between phases or between phases and ground, produces significant currents and can damage network equipment if not handled with adequate protection. This study aims to analyze and calculate short circuit fault currents in the electric power system using MATLAB and Simulink software . In this study, the electric power system model is simulated with various types of disturbances, namely three- phase , two -phase , and single -phase to ground disturbances , to determine the system response and the magnitude of the current that occurs. Power system parameter data such as voltage, component impedance, and load conditions are used as input in the modeling. The “ Three-Phase” block Fault ” in Simulink is used to implement a fault at a specific point in the system. The simulation results show that the magnitude of the fault current varies depending on the type of fault and the line impedance. With this analysis, system designers can determine the appropriate protection equipment, such as circuit breakers and relays , to prevent damage and maintain the stability of system operation. This study demonstrates the effectiveness of MATLAB as a simulation tool in power system fault analysis, providing practical and accurate solutions in fault current calculations.